2013
DOI: 10.4103/0972-2327.120496
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mirror therapy on lower extremity motor recovery, balance and mobility in patients with acute stroke: A randomized sham-controlled pilot trial

Abstract: Objective:To evaluate the effectiveness of mirror therapy on lower extremity motor recovery, balance and mobility in patients with acute stroke.Design:A randomized, sham-controlled, assessor blinded, pilot trial.Setting:Inpatient stroke rehabilitation unit.Subjects:First time onset of stroke with mean post-stroke duration of 6.41 days, able to respond to verbal instructions, and Brunnstrom recovery stage 2 and above were enrolled.Intervention:Mirror therapy group performed 30 minutes of functional synergy move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 26 publications
0
23
2
Order By: Relevance
“…This improvement is due to the time. These results did not support the initial hypothesis that mirror training would be more effective to improve balance compared non-mirror training, consistent with a recent clinical study in which the use of a mirror was proved not to be useful in improving balance [50]. The lack of between-group difference could probably be due to the short duration of administration of mirror visual feedback.…”
Section: Discussioncontrasting
confidence: 62%
“…This improvement is due to the time. These results did not support the initial hypothesis that mirror training would be more effective to improve balance compared non-mirror training, consistent with a recent clinical study in which the use of a mirror was proved not to be useful in improving balance [50]. The lack of between-group difference could probably be due to the short duration of administration of mirror visual feedback.…”
Section: Discussioncontrasting
confidence: 62%
“…It is important to emphasize that this intervention combined MT with bilateral training of LE movements which to our knowledge is the first post-stroke MT intervention for the LE to do so. While previous MT interventions for the UE incorporated bilateral movements [10], those for the LE have employed unilateral movement of the unaffected limb only [21], [22]. In the present study, participants demonstrated improved tolerance and endurance for bilateral MT training over the intervention period.…”
Section: Discussionmentioning
confidence: 58%
“…One randomized controlled trial (RCT) of a MT intervention that used ankle dorsiflexion movement for 5 days a week, 2 to 5 h a day, for 4 weeks in individuals with chronic stroke reported improved motor recovery and functional independence, but no difference in functional ambulation category (FAC) [21]. A second RCT included six LE-MT exercises for individuals with acute stroke for 30 min a day, six days a week, for two weeks [22]. Findings included improved ambulation as measured by FAC but no differences between groups in Brunnel Balance Assessment scores or motor recovery [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations